PREVALENCE OF AND SOCIO-ECONOMIC FACTORS INFLUENCING HONEY BEE STRESSORS AND THE COPING STRATEGIES IN BEE FARMS IN KWARA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
There has been a concern about declines in honeybees in the recent years including their pollination efficiency due to different factors, and this affect and reduce the production potential as related to every component of agricultural ecosystems. It is therefore imperative to describe prevalence of and socio-economic factors influencing honey bee stressors and the coping strategies in bee farms in Kwara State Nigeria. Descriptive statistics and multiple regression were used to analysed the data. A survey of various types of honey bee health stressors was conducted through structured questionnaire and a snowball sampling method was used to select the respondents. The honey bee pests and predators were surveyed and samples collected weekly from September 2013 to February 2014 from six apiaries and bee farms spread across ten LGAs. The result showed that the mean age of the respondents was 43 years which implies that beekeeping in the area is dominated by young managers. On human and environmentally induced bee stresses, bad apiary management practices, effect of pesticides usage and other human activity ranked most important in many apiaries in the LGAs studied. The study has also revealed that the farmers employ variety of stress management strategies: effective colony sanitation, improved human bee management and provision of adequate melliferous plant that provide bee nutrients all year round. It is recommended that training in bee farming and increase investment should be promoted among beekeepers to enable them imbibe improve techniques and acquired materials inputs that will translate into realistic quantity and quality.
Keywords: Coping strategy, honey bee pests, socioeconomic characteristics, stressors